The abdominal vacuum technique for bodybuilding - Rebullido, T. R.; Chulvi-Medrano, I. (Strength and Conditioning Journal, 2020)
The abdominal vacuum technique is a breath-holding maneuver used in bodybuilding to contrast a noticeable reduction of the waistline to an increase in thoracic circumference. This article provides a description of the abdominal vacuum exercise as well as a technique-driven progression and teaching cues for performing this maneuver.